The effects of wheat and yam flour diets on the toxicity of three botanical extracts to Tribolium castaneum (Herbst) and the underlying biochemical mechanisms - Emmanuel A. Oyeniyi; Ayodeji P. Akinnuoye (Heliyon)
This study investigates the interactive effects of food type, exposure time, and experimental dosages on the biochemical and insecticidal responses of Tribolium castaneum (Herbst) to the toxic effects of three botanicals. The botanicals [Piper guineense (PG), Cinnamomum verum (CV), and Syzygium aromaticum (SA)] were applied individually and in binary combinations (PG + SA, PG + CV, and SA + CV). Beetles were reared for two generations on wheat and yam flour prior to insecticide exposure. The specific activities of α-amylase, alkaline phosphatase (AKP), acid phosphatase (ACP), acetylcholinesterase (AChE), and glutathione S-transferase (GST) were also determined. Generally, the insecticidal and biochemical responses of T. castaneum to each botanical extract and their binary combinations varied with the type of host food used for rearing the beetles, the experimental dosage, and the exposure time to the extracts. The three main factors (i.e. food, time and dosage) and their two-way interactions (F∗D, F∗T and D∗T) significantly (p < 0.05) influenced the mortality response of the beetles. According to the LD50, LD95, and LT50 values, all three botanical extracts were generally more toxic to beetles fed wheat flour than those fed yam flour. Beetles given yam flour showed more toxic effects with the binary mixture of PG + CV and SA + CV than those fed wheat flour. Except for CV + SA, which had a synergistic effect on the mortality response of yam-reared T. castaneum, all the binary mixtures had antagonistic effects on the beetles' mortality rate. Irrespective of food type, significantly higher (p < 0.05) specific activities of α-amylase, AKP, and ACP was recorded in beetles exposed to CV alone and EA + CV combination relative to the control. This study demonstrates the valuable insights needed for the possible development of targeted and sustainable strategies for managing T. castaneum infesting wheat and yam flour.